Effect of stabilization splint therapy on glenoid fossa remodeling in temporomandibular joint osteoarthritis. Issue 4 (October 2016) - Ok, Soo-Min; Jeong, Sung-Hee; Ahn, Yong-Woo; Kim, Yong-Il
Abstract: Purpose: The aim of this study was to evaluate, by CBCT superimposition, bone changes (cortical bone intactness, sclerosis and subchondral cyst) in the glenoid fossa related to stabilization splint (SS) therapy for temporomandibular joint osteoarthritis (TMJ OA) patients and to compare the effects for two groups, one that had undergone SS therapy and the other that had not. Methods: This case–control study included 36 TMJ OA patients, 10 that had undergone SS therapy (the SS group) compared with 26 that had not (the non-SS group). Osseous changes in the glenoid fossa were evaluated based on superimposed CBCT images before and after treatment. Results: Improvements ranging from 57.5 to 100% were achieved in cortical bone integrity, sclerosis, and subchondral cyst for both groups, SS and non-SS. However, there were no statistically significant difference between the two groups ( p  > 0.05). The non-SS group showed a significant decrease in the distances from the point of inflexion and the lowest point of the articular eminence to the reference line ( p  < 0.05). On the other hand, the SS group showed an increase for the point of inflexion. The other measures showed no statistically significant differences in distance before treatment and after treatment, even though the average distance after treatment showed an overall increasing tendency. Conclusion: SS therapy relieved excessive loading on the TMJ in the TMD OA patients, who showed, via CBCT superimposition, less bone resorption in the glenoid fossa.